Particle transport and deposition in porous structures: effects of particle properties, porosity and Reynolds number - Kruz, S. (2012)
Since experiments are expensive and often difficult to perform reliable computational fluid dynamics (CFD) models save time and money when applied to transport and deposition of aerosol particles. In this work, we simulate particle transport and deposition in porous structures with different porosity. The resulting air-flow patterns as well as particle transport and deposition are analyzed for different inlet flows and particle with different properties (i.e., density and diameter). We compute particle trajectories and the deposition for different conditions. In addition, the loss of permeability due to deposition is evaluated.